2008
DOI: 10.1016/s0873-2159(15)30274-9
|View full text |Cite
|
Sign up to set email alerts
|

Influência de um programa de iniciação científica na produção científica de professores em curso de Medicina no Brasil

Abstract: After the inception of SIP, all professors had an increase in their scientific output; however, this occurred independently of their engagement in SIP disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
6
1
4
Order By: Relevance
“…There was a total of 23.33% with a Master's degree and 76.66% with a Doctorate degree. The prevalence of professors with a doctorate in PIC was higher than that found by Cyrillo et al 10 at the Universidade Federal Fluminense, in which 52.62% of the professors participating in a scientific initiation discipline had a doctorate and 21.54% had a Master's degree.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…There was a total of 23.33% with a Master's degree and 76.66% with a Doctorate degree. The prevalence of professors with a doctorate in PIC was higher than that found by Cyrillo et al 10 at the Universidade Federal Fluminense, in which 52.62% of the professors participating in a scientific initiation discipline had a doctorate and 21.54% had a Master's degree.…”
Section: Discussioncontrasting
confidence: 59%
“…When the publication of articles was compared between the Master's and Doctorate groups of professors, it was observed that the Master's group produced less scientific articles (p = 0.01). A similar study pointed out that Master's degree professionals have their research activity more limited and less encouraged because they cannot supervise graduate students 10 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…E as vantagens não se restringem aos alunos. Os professores que ingressam em programas de Iniciação Científica têm a possibilidade de aumentar sua produtividade, ou seja, seu número de publicações 5 . A Iniciação Científica trabalha, então, no aperfeiçoamento profissional do graduando, constituindo parte fundamental de um curso superior.…”
Section: Por Que Iniciação Científica?unclassified
“…Entre os pesquisadores médicos, a falta de orientação específica e de estímulo institucional, a inconsistência da produção científica, com impactos em sua qualidade e regularidade, não contribuem ao desenvolvimento acadêmico no ensino médico. Aliado a isso, o docente médico tende a acumular as funções político-administrativas, de clínico e de investigador, em detrimento da carreira acadêmica [3,4].…”
Section: Introductionunclassified